A urbanização fetichista: crise imanente, planejamento e reprodução capitalista do e no espaço - Thiago Andrade dos Santos (2020)
This thesis starts from the analysis of the urbanization process to apprehend fetishism and the immanent crisis to the process of capital reproduction. It’s needed to understand the crisis without fetishizing it. Therefore, the discussion about urbanization shows that it is not exactly an urban crisis, but the fact that the city has been fetishized, included in the whirlwind of the reproduction of capital in crisis. In this imbroglio, the urbanization process became the favorite way of using capital with difficulties of productive employment in the scope of capital circulation productively. As land and urban soil are not the fruits of labor, they have no value, they just enter the complex process of distributing the surplus value. The socially produced space enters the circulation of fragmented capital as property of the soil and desired for generating land rent. However, there are structural limits to these processes that alleviate crises by allocating surplus value to real estate investments that enables land rent. The structural crisis in the process of capital reproduction stops this process again and makes use of fictitious capital, generating large bubbles of future works that will not be realized. The crises, then, generate their spaces full of contradictions. The so-called spatial adjustments do not solve the contradictions of capital, they represent the increase of the crisis itself. In this sense, I call fetishistic urbanization, urbanization in charge of the State and capitals, which ignores work as if it were a mere appendage of production, not only of capital, but of the social space itself. The poverty of (and in) cities shows the immanent crisis and the realization of the fetish of capital, which presents itself as the master of its self-worth. Practical cases such as urban (re)qualifications have their abstract face, which is hidden behind the concreteness of their forms, functions, structures and processes. The restructuring of (and in) the Belo Horizonte space involves the search for type II urban differentiated rents, which goes through processes such as verticalization by increasing construction potentials. In the absence of stocks of cheap land, land rents are increased by increasing the building potential of real estate using instruments provided for in urban legislation such as Consortium Urban Operations. Urban legislation, although it appeared as an advance, expresses the fetish. It is an instance in which the State and capital are articulated in the production of urban space through subtle mechanisms that move the categories of capital in their conflicting reproduction. The State, through its urban policy instruments, is the one who mobilizes and conditions the space to support capital and makes it possible to raise the levels of capitalization of land rents. At this point, we can see why we should think about the concept of production also in a broad sense, since the production of space involves the materialization of a society in space and this implies the production of goods, but also of ideologies, laws, culture, ways of life and also of the social space itself.